Studying the effect of potassium fertilization and spraying with amino acids on the growth and productivity of tobacco plants (Virginia variety) - Ataaf, Obada (Latakia University Journal -Biological Sciences Series, 2025)
The experiment was implemented at the Stakhris Agricultural Research Station in Lattakia during the 2021 agricultural season, according to a randomized complete block design (RCBD) with three replicates for each treatment. The research aimed to study the effect of potassium fertilization and spraying with amino acids on the growth and productivity of the tobacco plant, the Virginia tobacco variety (Nicotiana tabacum var. Virginie vk51), where some morphological characteristics of the plant were studied (plant height (cm) and total leaf surface area (m2). /plant), and the content of air-dried tobacco leaves of some biochemical compounds (total protein, soluble sugars, and nicotine (%)).Using the second level of amino acids and also the second level of potassium fertilization (IK2A1) gave the best results, as this treatment was significantly superior to the rest of the treatments, as the value of plant height in this treatment reached (226 cm), which was reflected positively on The total leaf surface area of ​​the plant is (3.52 m²/plant). The qualitative characteristics of the dry tobacco leaf also improved, as the percentage of total protein and nicotine decreased and the percentage of total soluble sugars increased. Based on the above, it can be suggested to use the drip irrigation method with increasing the level of potassium fertilization due to the role it plays in Virginia tobacco, in addition to spraying with amino acids, due to their tangible role in stimulating growth in the Virginia variety and improving the quality of the resulting tobacco.